Domestic violence and its determinants among reproductive-age women in Sub-saharan Africa: a multilevel analysis of 2019–2024 demographic and health survey data - Girum Nakie; Gebresilassie Tadesse; Setegn Fentahun; Gidey Rtbey; Fantahun Andualem; Getasew Kibralew; Mulualem Kelebie; Mamaru Melkam; Techilo Tinsae; Mulat Awoke Kassa; Tekletsadik Tekleslassie Alemayehu; Muluken Yigezu; et al. (BMC Public Health)
Abstract Background Domestic violence is a global health issue that impacts health policies and initiatives, as well as women’s health, reproductive outcomes, and family well-being. It violates human rights, hinders gender equality, and requires a multifaceted approach. Studies in sub-Saharan Africa (SSA) reveal significant disparities across nations. This study utilizes data from the 2019–2024 Demographic and Health Survey (DHS) to determine the prevalence of domestic violence among reproductive-age women in Sub-Saharan African countries and its associated factors. Methods A cross-sectional study design was used through multilevel logistic regression analysis. A total of 67,764 women aged 15–49 were included in the study. To ensure representativeness, weighted estimates were applied in the analysis using STATA version 17. Statistically significant variables were identified using adjusted odds ratios (AOR) with a 95% confidence interval (CI). Results The overall prevalence of domestic violence among reproductive-age women in sub-Saharan African countries was found to be 38.14% (95% CI: 37.78–38.51). The highest and the lowest prevalence of domestic violence were observed in Sierra Leone and Mauritania, 60.72% and 18.70%, respectively. Across regions, the highest prevalence of domestic violence was observed in Central Africa (45.7%), while the lowest prevalence was observed in West Africa (35.34%). Factors associated with domestic violence included justifying wife beating, witnessing mother beaten by father, education status, current working status, smoking tobacco, marital status, being afraid of their partner, and having a partner who exhibited jealousy when the respondent talked with other men. In contrast, age (15–29 years old) is protective against domestic violence. Residence, media exposure, and regions were also community-level factors associated with domestic violence. Conclusion The prevalence of domestic violence among reproductive-age women in sub-Saharan African countries is high. Individual and community-related factors contribute significantly to violence. Strengthening legal protections, economic and social empowerment of women, and implementing community-based education programs for partners are recommended to reduce domestic violence in sub-Saharan African countries.